Comparative Study of Character Education Policies at MI Hidayatul Insan and SDN 3 Matesih - Muhammad Habib Rosyidi; Subar Junanto (PALAPA, 2025)
This study addresses the limited research on character education policies in Islamic and public elementary schools, despite their crucial role in shaping students’ moral and spiritual development. The research aims to analyze and compare how Madrasah Ibtidaiyah (MI) Hidayatul Insan and Sekolah Dasar Negeri (SDN) 3 Matesih design and implement character education policies in alignment with their institutional missions and cultural contexts. Employing a qualitative comparative case study design, the study selected both schools through purposive sampling. Data were gathered through in-depth interviews, classroom observations, and curriculum document analysis, and were analyzed thematically to uncover patterns of similarity and difference in policy implementation. Findings reveal that both institutions emphasize core values such as discipline, responsibility, politeness, and cooperation. However, MI Hidayatul Insan integrates character education with a strong focus on religious and spiritual values embedded in Islamic learning activities, while SDN 3 Matesih emphasizes civic and social values aligned with the national character education framework. The study concludes that institutional vision and religious orientation significantly shape the priorities and strategies of character education. The findings contribute theoretically to comparative studies between Islamic and public education systems and offer practical insights for policymakers and educators seeking to integrate religious and civic values more holistically into national character education policies. Future research is recommended to explore cross-regional or longitudinal analyses to evaluate the long-term impact of character education across diverse educational settings.